Presumed acute unilateral toxoplasma papillitis without vitritis: A case report - Aktaş, Kasım; Canleblebici, Mehmet; Balbaba, Mehmet; Yıldırım, Hakan (My University, 2024)
Ocular toxoplasmosis is the most common cause of infectious retinochoroiditis in humans. Atypical and unilateral presentations such as papillitis without vitritis are especially challenging for diagnosis. Here, we report a case of a 17-year-old man with unilateral Toxoplasma papillitis without vitritis. Fundus examination revealed unilateral inflammation in the right optic disc and peripapillary area. Toxoplasma immunoglobulin (Ig)M titer was positive and IgG negative. During the follow-up, while the IgM titer decreased, the IgG titer increased. After possible etiologies were excluded, the patient was diagnosed with presumed Toxoplasma papillitis with a complete absence of vitritis at presentation. The patient was treated with appropriate antiparasitic agents and good response was observed without recurrence.
Keywords: Papillitis; Ocular toxoplasmosis; Toxoplasma immunoglobulin M